Two-dimensional nanofluidic suppressing anion mobility toward dendrite-free lithium metal anode. (June 2022) - Pan, Linhai; He, Haiyong; He, Hualong
Abstract: Modification of separator with lithium-ion redistributor has been considered to be an effective strategy to evade lithium dendrite by evening lithium-ion concentration on electrode surface. According to the Sand equation, the mobility of anion is also critical to realizing smooth lithium deposition. Herein, a fast cation conductor layer was constructed by assembling exfoliated vermiculite sheets on commercial separator to form vermiculite composite separator (VCS). The negative surface charged 2D nanofluidic channels in VCS repel anions, blocking the shuttle of anions between electrodes. Nevertheless, lithium ions are attracted, and mobility is dramatically enhanced, which increases the lithium-ion transference numbers (tLi + ) and intrinsically improves the electrochemical performance. Resultantly, the Coulombic efficiency of Cu//Li battery with VCS is more than 96%, and the voltage polarization of symmetric battery is only a quarter of the commercial separator even at a high current density of 5 mA/cm 2 . Furthermore, the inorganic nature of the vermiculite sheet endows the VCS with excellent thermal stability. The superior electrochemical performance of VCS highlights the importance of constructing 2D nanofluidic channels and provides new avenues for the development of high-performance and long-lifespan lithium metal batteries. Graphical abstract: Image 1 Highlights: The single-ion conducting behavior render VCS with a high lithium-ion transference number (tLi +  = 0.78). The nanofluidic channels within VCS guarantee the strong redistribution capability of lithium-ion flux. The natural inorganic properties of vermiculite sheets endow VCS with superior thermal stability.